Length-Weight Relationship and Condition Factor of Introduced Red Devil Cichlid Amphilophus labiatus, in Lake Sentani, Indonesia - Ohee, Henderite L.; Mote, Norce; Rice, Michael A.; Sujarta, Puguh; Surbakti, Suriani (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
Papua’s freshwater ecosystems in the western part of New Guinea have begun to record widespread introductions of invasive species over the past decade. This lake's most dominant and common exotic species is Amphilophus labiatus (Günther, 1864). A study was conducted to document the length-weight relationship and condition factor of these fish in Lake Sentani. From June to August 2019, fish were caught using floating gillnets at six locations around the lake. Total length (TL) (mm), body depth (mm), and body weight (grams) were measured, and condition factor based on gender, body weight, and body length were observed in 345 fish, including 264 males and 81 males. The growth pattern of A. labiatus is positively allometric, with b values ranging from 3.19 to 3. 20 and coefficients of determination (r2) ranging from 0.84 to 0.87. Although the average body length of A. labiatus males was shorter than females, condition factor (CF) values were not significantly different between the sexes and ranged from 0. 64 to 2.03 (0.97 ± 1.17, mean ± SD). For males, it went from 0.67 to 1.19 (0.94 ± 0.13 mean ± SD). However, monthly CF data show a significant decrease in CF in August, suggesting that spawning events occur in late July or early August. A. labiatus grows well and colonizes habitats throughout Lake Sentani.